Optimizing Electrochemical Performance: A Study of Aqueous Electrolytes with Hemp-Derived Activated Carbon for Supercapacitors - Kanisorn Klangvijit; Khemjiranee Bowornthommatadsana; Mayuree Phonyiem Reilly; Teerayut Uwanno; Visittapong Yordsri; Michiko Obata; Masatsugu Fujishige; Kenji Takeuchi; Winadda Wongwiriyapan (ACS Omega, 2025)
electrolyte access.
Keywords: Supercapacitor Materials and Fabrication; Advanced battery technologies research; Advancements in Battery Materials